Micronutrients in Maternal and Infant Health Where We Are and Where We Should Go - Yu, Yunxian (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Maternal and infant nutrition has been on the global agenda as central to health, sustainable development, and progress in low- and middle-income countries. Micronutrients, which play a major role in the metabolism of macronutrients, cellular metabolism, and organ development of the fetus, are important for maintaining pregnancy and fetal growth. Besides, during pregnancy, there is an elevated demand for micronutrients, the excess or deficiency of which can result in an increased risk of pregnancy complications and adverse birth outcomes. As China is a rapidly developing country with a large population, micronutrient status and its influence on maternal and infant health have always been a concern. This Special Issue aimed to estimate the influence that micronutrients can have on maternal and infant health, which provides evidence for clinical interventions and government nutrition-related policies. Additionally, this Special Issue provides study directions for research on micronutrients among pregnant women and infants. In this Special Issue, original research articles and reviews were welcomed. Research areas include, but are not limited to, the following: Micronutrient status of pregnant women and infants; Relationship between micronutrients and pregnancy complications as well as birth outcomes.